The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1029/98wr01572
|View full text |Cite
|
Sign up to set email alerts
|

Field study and simulation of diurnal temperature effects on infiltration and variably saturated flow beneath an ephemeral stream

Abstract: Abstract. Two experiments were performed to investigate flow beneath an ephemeral stream and to estimate streambed infiltration rates. Discharge and stream-area measurements were used to determine infiltration rates. Stream and subsurface temperatures were used to interpret subsurface flow through variably saturated sediments beneath the stream. Spatial variations in subsurface temperatures suggest that flow beneath the streambed is dependent on the orientation of the stream in the canyon and the layering of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
94
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(105 citation statements)
references
References 14 publications
4
94
0
1
Order By: Relevance
“…This model has been employed successfully in previous investigations to estimate stream channel infiltration [e.g., Ronan et al, 1998;Constantz, 1998;Bartolino and Niswonger, 1999]. The two longest flow events (November 2000 andApril 2001) recorded during the monitoring period were used to calibrate the thermal (sediment heat capacity and saturated thermal conductivity) and hydraulic (saturated hydraulic conductivity and porosity) parameters within the model.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This model has been employed successfully in previous investigations to estimate stream channel infiltration [e.g., Ronan et al, 1998;Constantz, 1998;Bartolino and Niswonger, 1999]. The two longest flow events (November 2000 andApril 2001) recorded during the monitoring period were used to calibrate the thermal (sediment heat capacity and saturated thermal conductivity) and hydraulic (saturated hydraulic conductivity and porosity) parameters within the model.…”
Section: Methodsmentioning
confidence: 99%
“…Exact matches were not considered possible given the simplicity of the model and the difference between a point scale core measurement and a field parameter. On the basis of previous sensitivity analyses by Ronan et al [1998] and Bailey [2002], the saturated hydraulic conductivity was considered the most sensitive parameter for modeling coupled heat transport and water flow. The lowest model residuals were found with the parameters shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…That study demonstrated qualitatively that the effect of temperature was the main reason for the variability in daily streamflow losses. Ronan et al (1998) also studied diurnal fluctuations in seepage rates and included numerical modeling results in their study. Bravo and Jiang (2002) applied a coupled groundwater flow and heat transport model to account for the dependence of water density and viscosity on temperature.…”
Section: Introductionmentioning
confidence: 99%